Constitutive Endocytosis of the Neuronal Glutamate Transporter Excitatory Amino Acid Transporter-3 Requires ARFGAP1 - Saha, Kusumika; Yang, Jae-Won; Hofmaier, Tina; Venkatesan, SanthoshKannan; Steinkellner, Thomas; Kudlacek, Oliver; Sucic, Sonja; Freissmuth, Michael; Sitte, Harald H. (Frontiers in Physiology, 2021)
The eukaryotic endocytic pathway regulates protein levels available at the plasma membrane by recycling them into specific endosomal compartments. ARFGAP1 is a component of the coat protein I (COPI) complex but it also plays a role in promoting adapter protein-2 (AP-2) mediated endocytosis. The excitatory amino acid transporter-3 (EAAT3) mediates the reuptake of glutamate from the synaptic cleft to achieve rapid termination of synaptic transmission at glutamatergic synapses. In this study, we identified two interacting proteins of EAAT3 by mass spectrometry (MS) ARFGAP1 and ARF6. We explored the role of ARFGAP1 and ARF6 in the endocytosis of EAAT3. Our data revealed that ARFGAP1 plays a role in the recycling of EAAT3, by utilizing its GTPase activating protein (GAP) activity and ARF6 acting as the substrate. ARFGAP1 promotes cargo sorting of EAAT3 via a single phenylalanine residue (F508) located at the C-terminus of the transporter. ARFGAP1-promoted AP-2 dependent endocytosis is abolished upon neutralizing F508. We utilized a heterologous expression system to identify an additional motif in the C-terminus of EAAT3 that regulates its endocytosis. Impairment in endocytosis did not affect somatodendritic targeting in cultured hippocampal neurons. Our findings support a model where endocytosis of EAAT3 is a multifactorial event regulated by ARFGAP1, occurring via the C-terminus of the transporter, and is the first study to examine the role of ARFGAP1 in the endocytosis of a transport protein.